Effect of modified feeding practice on milk production of cross bred dairy cows in Baghabari milk shed area, Sirajgonj (Asian Journal of Medical and Biological Research, 2015)
A research work was undertaken to find out alternative feeding practices for dairy cows in Baghabari milk shed areas. The trial was conducted in the village Alokdiar, Shajadpur, Sirajgonj. Twenty cross bred lactating dairy cows of 340 ±15.5 kg live weight were used for the trial. Animals were equally and randomly allocated dietary into four groups, T0 (Rice straw + concentrate), T1 (Napier silage + concentrate), T2 (Khesari hay + concentrate) and T3 (UMS + concentrate). There was no significant difference in total DM intake among the four groups. The DCP (kg/d) intake was significantly (P